Mindful, neurotic, or both: efficacy of online single-session mindfulness - Mohd Zahid Juri, (Penerbit Universiti Kebangsaan Malaysia, 2019)
With the popularity of online websites and apps that use mindfulness audio recording to teach mindfulness practice, it piqued our interest to examine how online mindfulness resources like Headspace can be helpful to the non-clinical population. The current study aimed to investigate the efficacy of brief (15 min) single-session mindfulness on attention regulation (as measured by word-colour Stroop task). In response to the limitations outlined in previous studies, we also examine the moderation effect of two individual differences (i.e., neuroticism and dispositional mindfulness). This experimental design randomly assigned the participants into either the experimental (Headspace) or control group (audiobook recording). Their level of neuroticism and dispositional mindfulness were measured by using the IPIPNEO-120 and MAAS scale respectively. Results indicate that, in the experiment group, participants’ attention regulation on different levels of neuroticism varied across different level of dispositional mindfulness. However, the patterns of the results were not as expected. This study has shown that in general a single-session mindfulness might not be efficacious in enhancing attention regulation. However, there were specific groups of personality traits that benefitted from it.